Movement disorders in valine métabolism diseases caused by HIBCH and ECHS1 deficiencies. (9th August 2022) - François‐Heude, Marie‐Céline; Lebigot, Elise; Roze, Emmanuel; Warde, Marie Thérèse Abi; Cances, Claude; Damaj, Lena; Espil, Caroline; Fluss, Joel; de Lonlay, Pascale; Kern, Ilse; Lenaers, Guy; Munnich, Arnold; et al.
Abstract: Background and purpose: HIBCH and ECHS1 genes encode two enzymes implicated in the critical steps of valine catabolism, 3‐hydroxyisobutyryl‐coenzyme A (CoA) hydrolase (HIBCH) and short‐chainenoyl‐CoA hydratase (ECHS1), respectively. HIBCH deficiency (HIBCHD) and ECHS1 deficiency (ECHS1D) generate rare metabolic dysfunctions, often revealed by neurological symptoms. The aim of this study was to describe movement disorders spectrum in patients with pathogenic variants in ECHS1 and HIBC . Methods: We reviewed a series of 18 patients (HIBCHD: 5; ECHS1D: 13) as well as 105 patients from the literature. We analysed the detailed phenotype of HIBCHD (38 patients) and ECHS1D (85 patients), focusing on MDs. Results: The two diseases have a very similar neurological phenotype, with an early onset before 10 years of age for three clinical presentations: neonatal onset, Leigh‐like syndrome (progressive onset or acute neurological decompensation), and isolated paroxysmal dyskinesia. Permanent or paroxysmal MDs were recorded in 61% of HIBCHD patients and 72% of ECHS1D patients. Patients had a variable combination of either isolated or combined MD, and dystonia was the main MD. These continuous MDs included dystonia, chorea, parkinsonism, athetosis, myoclonus, tremors, and abnormal eye movements. Patients with paroxysmal dyskinesia (HIBCHD: 4; ECHS1D: 9) usually had pure paroxysmal dystonia with normal clinical examination and no major impairment in psychomotor development. No correlation could be identified between clinical pattern (especially MD) and genetic pathogenic variants. Conclusions: Movement disorders, including abnormal ocular movements, are a hallmark of HIBCHD and ECHS1D. MDs are not uniform; dystonia is the most frequent, and various types of MD are combined in single patient. Abstract : Flow chart.